The role of Islamic organizations in Development and Enforcement of Islamic Law in Indonesia - Agus Miranto; Kurniati Kurniati; Abd Rahman (International Journal on Advanced Science, Education, and Religion, 2022)
Before the 1945 Constitution came into force , law marriage and inheritance already applied for Indonesian Muslims . Condition Islamic society in Indonesia which is the majority is very possible enforcement and enforcement Islamic law . With application expected Islamic law crisis multidimensional happening _ could handled by the State. order values Islamic law applies in a manner intact in society , then values that Islamic law must poured in form law . History records that presence Islamic organizations such as Sarekat Islam (SI), Muhammadiyah, Nahdhatul Ulama (NU) and MUI are very influential to birth sharia rules that have there is moment this . So this post discuss how role internal Islamic organizations implementation and development Islamic law in order to be able to enforced by the national Islamic society .